(untitled) (Cardiovascular Journal, 2022)
Background: Early detection and appropriate management play a key role in reducing the morbidity and mortality of acute heart failure in patients with acute myocardial infarction. Many prognostic factors have been assessed till date. This study aimed to evaluate the prognostic effect of NLR on in-hospital outcomes in patients with acute heart failure due to acute anterior ST elevation myocardial infarction. Methods: The present study was carried out in the Department of cardiology, Sir Salimullah Medical College & Mitford Hospital, Dhaka from January 2020 to December 2020. A total of 88 cases of acute heart failure due to acute anterior ST elevation Myocardial infarction patients are enrolled in this study. NLR was estimated and patients were divided into two groups based on the NLR (Group I NLR <6; Group II NLR ≥6). Then in-hospital outcome was observed and compared between two groups. Results: In-hospital mortality and length of hospital stay were higher among NLR ≥6 patients with statistical significance (11.6% vs. 40.9%, p<0.001). These patients also had high incidence of cardiogenic shock (25% vs. 43%, p>0.072), Arrhythmia (18% vs. 34%, p>0.089) but without statistically significant difference. Conclusion: In this study, we observed that in-hospital outcomes were worse in patients with acute heart failure due to acute anterior myocardial infarction with NLR ≥6. So NLR can be used as a predictor of outcome in acute heart failure patients. This association is independent of conventional cardiovascular risk factors. Cardiovasc j 2022; 15(1): 13-19